Economic gains from introducing international ITQs—The case of the mackerel and herring fisheries in the Northeast Atlantic. (September 2015) - Thøgersen, Thomas; Eigaard, Ole Ritzau; Fitzpatrick, Mike; Mardle, Simon; Andersen, Jesper Levring; Haraldsson, Gunnar
Abstract: Achieving a balance between fishing capacity and fishing opportunities is one of the major challenges in European fisheries. One way to achieve this is to introduce individual tradable quotas or similar management measures. In several mackerel and herring fisheries in the Northeast Atlantic, such systems have already been introduced on a national basis and the long term economic gains of this have been acknowledged. This paper takes this a step further and investigates the potential economic gains from introducing individual tradable quotas between countries. Overall, the results show that the gross cash flow can be improved by 21% by allowing the mackerel and herring quotas to be traded internationally in the Northeast Atlantic. This rent gain arises mainly from increased productivity by allowing tradability between areas and fleets. The analysis also shows that the Danish pelagic fleet will gain from increasing its share of mackerel and herring quotas, whereas the Irish fleets are incentivised to sell quota, if individual quotas are allowed to be traded among countries. This result is in line with the qualitative analyses that show that Irish fishermen targeting herring in the Celtic Sea are negatively oriented towards international individual tradable quotas, whereas the Danish pelagic fishermen have strong preferences for international individual tradable quotas.